Two novel cases with PIGQ-CDG: expansion of the genotype–phenotype spectrum and evaluation of GestaltMatcher as a diagnostic tool - Kušíková, Katarína; Hsieh, Tzung-Chien; Pfeifer, Mateja; Fauth, Christine; Murakami, Yoshiko; Laccone, Franco; Karall, Daniela; Bonfig, Walter; Stewart, Helen; Weis, Denisa (Frontiers in Genetics, 2025)
IntroductionThe glycosylphosphatidylinositol (GPI) anchor is a glycolipid that anchors proteins to the eukaryotic cell surface. An anchoring process is a posttranslational modification of at least 150 molecules with various functions. Biallelic causal variants in the PIGQ gene (OMIM: * 605754) are associated with a type of disorder of glycosylphosphatidylinositol biosynthesis (PIGQ-congenital disorders of glycosylation (CDGs), also called multiple congenital anomalies-hypotonia-seizures syndrome 4 (MCAHS4, OMIM: # 618548). Only 11 patients with this condition have been reported to date.MethodsWe present two novel cases of MCAHS4 with one novel and one already known variant in the PIGQ gene, detailed phenotyping, and a review of all published cases so far. We used GestaltMatcher for deep gestalt analysis and investigated its potential use in diagnosing MCAHS4 patients.ResultsIn the PIGQ gene, we found one novel frameshift variant c.1092dupC, p.(Phe365LeufsTer78) and one missense c.1370T>G, p.(Leu457Arg) already listed in the ClinVar database as a variant of uncertain significance (VUS), whose pathogenicity we proved by a functional study on Chinese hamster ovarian cells. After reviewing all 13 already diagnosed MCAHS4 patients, we found that attacks of rhabdomyolysis induced by a febrile infection were documented only in our patient. Facial dysmorphism (coarse features, anteverted nares, and open mouth) seen in all analyzed MCAHS4 patients seems to be specific. Moreover, GestaltMatcher proved that MCAHS4 patients shared a similar facial phenotype.DiscussionThe present work expands the genotype spectrum by describing a novel causal PIGQ variant and validating the pathogenicity of an already-known VUS variant. Because of their life-threatening complications, attacks of rhabdomyolysis should be considered in MCAHS4 patients. GestaltMatcher can be an effective tool in the diagnostic setting of MCAHS4.